2015
DOI: 10.1002/mnfr.201500048
|View full text |Cite
|
Sign up to set email alerts
|

Dose effect on the uptake and accumulation of hydroxytyrosol and its metabolites in target tissues in rats

Abstract: Hydroxytyrosol (HT) is the most prominent phenolic compound of virgin olive oil and due to its scientifically validated biological activities it is entering to the market as a potentially useful supplement for cardiovascular disease prevention. The aim of the present study was to investigate the relationship between the HT dose intake and its tissue uptake in rats, and thus, providing complementary information in relation to the target-dose relationship. Rats were given a refined olive oil enriched with HT at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 21 publications
(24 reference statements)
9
50
0
Order By: Relevance
“…Identification studies carried out with the authentic standards revealed that both isomers (hydroxytyrosol-3-sulphate and hydroxytyrosol-4-sulphate) were present (data not shown). It must be underlined that most of the previous studies [18][19][20]41] were performed measuring polyphenols and their metabolites immediately after the administration of high doses of polyphenols. To the best of our knowledge, to date no research has reported residue levels of these compounds in meat of food-producing animals within an on-farm trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification studies carried out with the authentic standards revealed that both isomers (hydroxytyrosol-3-sulphate and hydroxytyrosol-4-sulphate) were present (data not shown). It must be underlined that most of the previous studies [18][19][20]41] were performed measuring polyphenols and their metabolites immediately after the administration of high doses of polyphenols. To the best of our knowledge, to date no research has reported residue levels of these compounds in meat of food-producing animals within an on-farm trial.…”
Section: Resultsmentioning
confidence: 99%
“…However, these techniques are still used to analyze polyphenols in food of animal and vegetal origin [16,17]. Sample preparation plays a pivotal role in polyphenol analysis, especially when low concentrations (parts per billions) have to be detected and quantified: a clean-up step with SPE cartridges is generally provided after analyte extraction with polar solvents [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Granados-Principal et al [106] found in cardiac tissue that HT (0.5 mg/kg, 5 days/week × 6 weeks) increases expression of mitochondria complexes 1, 2 and 3 and reduces specific markers of oxidative damages to proteins. These HT beneficial effects on cardiac function are probably due to its antioxidative properties (0.1 and 10 µg/mL) [109], since HT was not found in rat heart (1, 10 and 100 mg/kg) [138]. …”
Section: Associated Complications: Oxidative Stress Inflammationmentioning
confidence: 99%
“…Because DOPET is a neutral alcohol, exogenously administered DOPET would be expected to diffuse readily within the total body water space and enter central neurons; and because DOPET is a catechol, intracellular DOPET would be expected to act as an anti-oxidant. Consistent with these expectations, oral administration of DOPET to rats results in dose-related increases in brain tissue levels of DOPET and its metabolites [15], and after systemic injection DOPET is detected in striatal microdialysate [16]. Systemically administered DOPET prevents the increases in lipid peroxides and the decreases in reduced glutathione levels in striatum that are evoked by 3-nitropropionic acid [17], indicating an ability to exert anti-oxidant effects in central dopaminergic neurons.…”
mentioning
confidence: 89%